Air non-thermal plasma treatment of Irgarol 1051 deposited on TiO2. (November 2018) - Giardina, Agata; Tampieri, Francesco; Marotta, Ester; Paradisi, Cristina
Abstract: The herbicide 2-(methylthio)-4-( tert -butylamino)-6-(cyclopropylamino)- s -triazine (tradename Irgarol 1051, abbreviated here as Irg), widely used in antifouling paints as biocide inhibiting seaweeds growth, is found in coastal waters in the vicinity of ports and harbors. In this work, Irg was subjected to air non-thermal plasma (NTP) treatment, alone and in the presence of TiO2 . A dielectric barrier discharge reactor was used, powered by AC voltage (18 kV, 50 Hz) to produce air-NTP directly above the surface of the aqueous Irg solution to be treated. Due to the very fast degradation of Irg occurring under the experimental conditions used, the results of kinetic experiments failed to detect any rate enhancement due to titania induced photodegradation. We show, however, that pre-adsorption of Irg on titania provides a means to significantly increase Irg NTP-induced degradation throughput, a result which might have useful practical consequences. It is concluded that this phenomenon is due to the acidic character of TiO2 which brings more Irg in solution by increasing the value of the ionization ratio, [IrgH + ]/[Irg] . Product analysis, performed by LC/ESI-MS n, allowed us to detect and identify numerous intermediates of Irg degradation and to propose different competing reaction pathways for the investigated NTP induced Irg advanced oxidation process. The extent of mineralization to CO2 was assessed by Total Carbon analysis. It was found to reach 95% after 5 h treatment of Irg solutions with an initial concentration of 5·10 −6 M. These results confirm the capability of our NTP prototype reactor to mineralize persistent organic pollutants. Graphical abstract: Image 1 Highlights: Pre-adsorption of Irgarol on TiO2 increases throughput of plasma induced degradation. Acidic character of TiO2 brings more Irgarol in solution by protonation. The intermediate products formed from plasma degradation of Irgarol are characterized. Almost total conversion of Irgarol to CO2 was achieved by plasma degradation.